Contemporary challenges to iodine status and nutrition: the role of foods, dietary recommendations, fortification and supplementation. Issue 3 (29th April 2018) - Bouga, M.; Lean, M. E. J.; Combet, E.
Abstract : Iodine deficiency (ID) in women of childbearing age remains a global public health concern, mainly through its impact on fetal and infant neurodevelopment. While iodine status is improving globally, ID is still prevalent in pregnancy, when requirements increase. More than 120 countries have implemented salt iodisation and food fortification, strategies that have been partially successful. Supplementation during pregnancy is recommended in some countries and supported by the WHO when mandatory salt iodisation is not present. The UK is listed as one of the ten countries with the lowest iodine status globally, with approximately 60 % of pregnant women not meeting the WHO recommended intake. Without mandatory iodine fortification or recommendation for supplementation in pregnancy, the UK population depends on dietary sources of iodine. Both women and healthcare professionals have low knowledge and awareness of iodine, its sources or its role for health. Dairy and seafood products are the richest sources of iodine and their consumption is essential to support adequate iodine status. Increasing iodine through the diet might be possible if iodine-rich foods get repositioned in the diet, as they now contribute towards only about 13 % of the average energy intake of adult women. This review examines the use of iodine-rich foods in parallel with other public health strategies, to increase iodine intake and highlights the rare opportunity in the UK for randomised trials, due to the lack of mandatory fortification programmes.